2015
DOI: 10.1371/journal.pone.0130030
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Based and Molecular Assessment of Bacterial Diversity in the Rhizosheath of Wheat under Different Crop Rotations

Abstract: A field study was conducted to compare the formationand bacterial communities of rhizosheaths of wheat grown under wheat-cotton and wheat-rice rotation and to study the effects of bacterial inoculation on plant growth. Inoculation of Azospirillum sp. WS-1 and Bacillus sp. T-34 to wheat plants increased root length, root and shoot dry weight and dry weight of rhizosheathsoil when compared to non-inoculated control plants, and under both crop rotations. Comparing both crop rotations, root length, root and shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 60 publications
(130 reference statements)
4
45
0
2
Order By: Relevance
“…reduced pH from 7.0 to 4.8±0.2 of the Pikovskaya broth medium supplemented with TCP (Table 3) and solubilised maximum amount of phosphorous (355±14 µg/mL). Association and isolation of phosphate solubilising Bacillus strains from the rhizosphere of various crops like wheat, rice, sugarcane and maize has been frequently reported (Tahir et al, 2015;Tahir et al, 2013). Two bacterial strains Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…reduced pH from 7.0 to 4.8±0.2 of the Pikovskaya broth medium supplemented with TCP (Table 3) and solubilised maximum amount of phosphorous (355±14 µg/mL). Association and isolation of phosphate solubilising Bacillus strains from the rhizosphere of various crops like wheat, rice, sugarcane and maize has been frequently reported (Tahir et al, 2015;Tahir et al, 2013). Two bacterial strains Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 97%
“…The reason for this may be the soil factors like temperature, moisture, aeration, root exudates nature and indigenous bacterial population at that specific plant growth stage was more suitable for the growth, survival and activity of the Pseudomonas strain. Previous studies have reported that the population, diversity, survival and activity of bacteria is affected due to nature of root exudates and indigenous rhizosphere bacteria (Shridhar, 2012;Tahir et al, 2015;Walker et al, 2003). Both the bacterial strains, Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These bacteria also produce the siderophores and synthesize enzymes, antibiotics, or fungicidal compounds that protect the plants against phytopathogenic microorganisms [63,64]. There are several factors such as agricultural practices, plant genotype, bacteria species, and strain that may affect the success of inoculation and plant response to these PGPB [65,66]. Chickpea and Rhizobium leguminosrum subsp.…”
Section: Influence Of Coinoculation On Bioavailability Of Micronutrientsmentioning
confidence: 99%